Fashion, Bodies, and Objects - Jean-François Fourny (Studies in 20th & 21st Century Literature, 1996)
This essay is based on the assumption that the body has undergone a process of fragmentation that started with "modern" art and commodity fetishism that is being amplified today by an increasingly fetishistic high fashion industry itself relayed by music videos and a gigantic pornography industry. This article begins with a discussion of fetishism and objectification as they appear in high fashion shows where underwear becomes wear (turning the inside into the outside), thus expanding (or dissolving) the traditional notion of pornography because they are both reported in comparable terms by mainstream magazines such as Femmes and less conventional publications such as Penthouse. A comparable phenomenon takes place in the novels of Hervé Guibert where internal organs (that is the inside) become literary characters (as "outside") through medical imagery. Finally, an issue of the French New Look magazine is analyzed because it features a high fashion collection next to a pictorial/essay on Issei Sagawa, a.k.a. "the Japanese Cannibal." Here again, the objectification of the dismembered body is taken a step further both by designer Jean-Paul Gaultier and Sagawa. It thus appears that the human body is nowadays being totally invested by commodity fetishism, rendering gender difference obsolete and opening a new space that so far has no name, and announces the final merging of high fashion, literature, pornography, and music videos.
Keywords: body; fragmentation; high fashion; fetishism; objectification; pornography; Femmes; Penthouse; Hervé Guibert; medical imagery; inside; outside; New Look; Issei Sagawa; the Japanese Cannibal; Jean-Paul Gaultier; human body; dismemberment; fashion; objects; gender; music videos